Pola Sebaran Plankton Secara Horizontal Di Perairan Desa Ohoililir, Kabupaten Maluku Tenggara - Fabian N. J Souisa; Erna Almohdar (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2017)
Plankton is divided into two classes namely phytoplankton and zooplankton, where phytoplankton is microscopic plants that buoyant and float in the upper part of the ocean, whereas herbivor and carnivore zooplankton have more planktonic characteristic. This research aimed to figure plankton distribution pattern horizontally in Ohoililir water, Southeast Maluku Regency. Collecting data conducted on October, 2015 by using plankton net with 80 μm mesh size on four stations. Total Profusion plankton were around 1,785,000-3,015,000 sel/m3 which the most dominant zooplankton found were from crustacean class and Branchionusangularis genus as high as 49,000 sel/m3. The highest profusion was on second station and the lowest was on fourth station. Highest distribution pattern horizontally was on second station with profusion value more than 30.000 sel/m3.